The Costs and Benefits of Two Secondary Symbionts in a Whitefly Host Shape Their Differential Prevalence in the Field - Shan, Hong-Wei; Liu, Shu-Sheng (Frontiers in Microbiology, 2021)
Insects commonly harbour maternally inherited intracellular symbionts in nature, and the microbial partners often exert influence on host reproduction and fitness to promote their prevalence. Here, we investigated composition of symbionts and their biological effects in the invasive Bemisia tabaci MED species of a whitefly complex. Our field surveys revealed that populations of the MED whitefly, in addition to the primary symbiont Portiera, mainly contain two secondary symbionts Hamiltonella, which is nearly fixed in the host populations, and Cardinium with infection frequencies ranging from 0-86%. We isolated and established Cardinium-positive and Cardinium-free whitefly lines with a similar nuclear genetic background from a field population, and compared performance of the two whitefly lines. The infection of Cardinium incurred significant fitness costs on the MED whitefly, including reduction of fecundity and egg viability as well as delay in development. We then selectively removed Hamiltonella from the Cardinium-free whitefly line and compared performance of two whitefly lines, one harbouring both Portiera and Hamiltonella and the other harbouring only Portiera. While depletion of Hamiltonella had little or only marginal effects on the fecundity, developmental rate, and offspring survival, the Hamiltonella-free whitefly line produced very few female offspring, often reducing the progeny female ratio from about 50% to less than 1%. Our findings indicate that the varying costs and benefits of the association between these two symbionts and the MED whitefly may play an important role in shaping their differential prevalence in the field.